Sex Differences in Asthma: A Key Role of Androgen-Signaling in Group 2 Innate Lymphoid Cells - Laffont, Sophie; Blanquart, Eve; Guéry, Jean-Charles (Frontiers in Immunology, 2017)
Infectious diseases, autoimmune diseases, and also allergy differentially affect women and men. In general, women develop strongest immune responses and thus the proportion of infected individuals and the severity of many viral, bacterial, or parasitic infections are increased in men. However, heightened immunity in women makes them more susceptible than men to autoimmunity and allergy. While sex differences in immunity are well documented, little is known about the cellular and molecular mechanisms underlying these immunological differences, particularly in allergic asthma. Asthma is a chronic inflammation of the airways mediated by exacerbated type 2 immune responses. Sex differences have been reported in the incidence, prevalence, and severity of asthma. While during childhood, males are more susceptible to asthma than females, there is a switch at the onset of puberty as for many other allergic diseases. This decrease of asthma incidence around puberty in males suggests that hormonal mediators could play a protective role in the susceptibility to allergic responses in male. Group 2 innate lymphoid cells (ILC2s) have recently emerged as critical players in the initiation of allergic responses, but also in the resolution of parasitic infection, through their capacity to rapidly and potently produce type 2 cytokines. This review will cover the current understanding of the impact of sex-linked factors in allergic inflammation, with a particular focus on the role of sex hormones on the development and function of tissue-resident ILC2s.